Social media use for patient care: An evaluation of health practitioners in Cross River State, Nigeria. - Veronica Akwenabuaye Undelikwo (International Journal of Public Health Science (IJPHS), 2022)
This study aimed to evaluate the extent to which health practitioners in Cross River State, Nigeria, use social media for patient care and to assess the barriers militating against its liberal use for patient care. The study adopted the cross-sectional survey design and used 550 respondents selected through the cluster, simple random and purposive sampling techniques, from selected secondary and tertiary health facilities. Furthermore, quantitative and qualitative methods involving the questionnaire and key informant interview respectively were used to elicit information from respondents. Quantitative data were analyzed using descriptive statistics while content analysis was used to handle qualitative data. The result of data analysis revealed that health practitioners in Cross River State, Nigeria, do social media use for patient care very minimally and this is attributed to a wide range of factors, including the absence of a clear-cut regulatory framework governing social media use in health care delivery, lack of institutionally provided resources for social media use etc. The study thus recommends that healthcare administrators must, as a matter of necessity, mainstream social media use into health care practice by flexible guidelines, regulations, and materials that would make social media use for patient care desirable by health practitioners in Nigeria.